Analisis Kadar Fosfor (P) Pada Pupuk Organik Cair Dari Limbah Buah Dengan Variasi Jenis Bioaktivator (Ragi Tape Dan EM-4) - Muhammad Difhari; Mikhratunnisa Mikhratunnisa (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Organic waste is waste that can be decomposed such as food scraps, fruit, leaves, and so on. One of the factors that affect the environment is the problem of waste disposal and management. There are various ways to overcome the problem of organic waste, one of which is by processing organic waste into liquid organic fertilizer. In this research, the manufacture of liquid organic fertilizer used waste of banana peels, pineapple peels and dragon fruit peels with the addition of tape yeast and EM-4 bioactivators. The purpose of this study was to determine the effect of bioactivator concentration and type of bioactivator on phosphorus content in liquid organic fertilizer. The method used in this study is an experimental method using a randomized block design. Based on the results of the study, it was found that the concentration of bioactivators did not affect phosphorus levels in liquid organic fertilizer, but the type of bioactivator affects the phosphorus content in liquid organic fertilizer. but the type of bioactivator affects the phosphorus content in liquid organic fertilizer. The addition of 5 ml, 10 ml and 15 ml of EM-4 bioactivator resulted in phosphorus levels of 204.35 ppm, 217.85 ppm and 215.87 ppm respectively. The addition of 5 ml, 10 ml and 15 ml of tape yeast bioactivator resulted in phosphorus levels of 156.53 ppm, 134.07 ppm and 136.21 ppm respectively. The best treatment obtained in this study was the addition of 10 ml of EM-4 bioactivator, but the levels of phosphorus produced do not meet the standards of the Ministry of Agriculture No. 28 of 2009.